Field reports of Iowa birds contributed by Thomas H. Kent, November 29, 1986 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1986)
List of birds and locations contributed by Thomas H. Kent with observers Francis L. Moore, Robert I. Cecil, Carl J. Bendorf and others. The field notes include several bird descriptions. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1986. Epson - sheet feed